2014
DOI: 10.1140/epje/i2014-14124-0
|View full text |Cite
|
Sign up to set email alerts
|

Optically driven oscillations of ellipsoidal particles. Part I: Experimental observations

Abstract: We report experimental observations of the mechanical effects of light on ellipsoidal micrometre-sized dielectric particles, in water as the continuous medium. The particles, made of polystyrene, have shapes varying between near disk-like (aspect ratio k = 0.2) to very elongated needle-like (k = 8). Rather than the very tightly focused beam geometry of optical tweezers, we use a moderately focused laser beam to manipulate particles individually by optical levitation. The geometry allows us varying the longitud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
14
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 51 publications
0
14
0
Order By: Relevance
“…These particles are trapped at the focal point of a tightly focused by optical gradient forces. Several applications of this non-contact particle manipulation have been considered ranging from movement tracking [8][9][10], application or detection of small forces [11,12], altering cell membranes [13][14][15], cells sorting [16][17][18] and particles manipulation [19][20][21][22][23][24], to name a few. This last application, which is the most popular one, includes dielectric spheres, viruses, bacteria, organelles, or DNA stands manipulation.…”
Section: Introductionmentioning
confidence: 99%
“…These particles are trapped at the focal point of a tightly focused by optical gradient forces. Several applications of this non-contact particle manipulation have been considered ranging from movement tracking [8][9][10], application or detection of small forces [11,12], altering cell membranes [13][14][15], cells sorting [16][17][18] and particles manipulation [19][20][21][22][23][24], to name a few. This last application, which is the most popular one, includes dielectric spheres, viruses, bacteria, organelles, or DNA stands manipulation.…”
Section: Introductionmentioning
confidence: 99%
“…The latter have, only recently, been experimentally observed [22]. In addition, their geometric anisotropy allows angular momentum to be exchanged with optical fields, permitting ellipsoidal particles to be oriented or rotated [23][24][25][26][27][28][29][30][31][32]. A number of applications follow from these properties.…”
Section: Introductionmentioning
confidence: 99%
“…To predict the optical forces on particles with low symmetry, however, requires extensive numerical calculations, such as the T-matrix method 4 and the discrete dipole approximation 5 . Previous works have shown that non-spherical particles can be aligned along a limited equilibrium orientation when trapped with a Gaussian beam 6 7 and their position and orientation were measured by holographic microscopy techniques 8 9 , and have exhibited unstable motion, depending on the sample geometry and optical properties 10 11 . Since optical trapping is an example of light–matter interaction, methods of controlling the stable orientation of arbitrarily shaped particles can be explored either by modifying sample shapes or by engineering the wavefront of light 12 .…”
mentioning
confidence: 99%